2022
DOI: 10.3389/fimmu.2022.1004439
|View full text |Cite
|
Sign up to set email alerts
|

Activation of NOD1 and NOD2 in the development of liver injury and cancer

Abstract: Hepatocytes and liver-resident antigen-presenting cells are exposed to microbe-associated molecular patterns (MAMPs) and microbial metabolites, which reach the liver from the gut via the portal vein. MAMPs induce innate immune responses via the activation of pattern recognition receptors (PRRs), such as toll-like receptors (TLRs), nucleotide-binding oligomerization domain 1 (NOD1), and NOD2. Such proinflammatory cytokine responses mediated by PRRs likely contribute to the development of chronic liver diseases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 59 publications
(154 reference statements)
0
6
0
1
Order By: Relevance
“…Pathway enrichment study identified the activation of NOD1/NOD2 in liver tissues of the heat stress group which triggers proinflammatory and type I interferon responses, contributing to liver injury. These receptors play a role in recognizing bacterial pathogens, inducing liver inflammation, and have associations with innate immune activation in metabolic diseases, with studies suggesting that blocking NOD1 can be protective against tissue injury 61 , 62 . TREM-1 (Triggering Receptor Expressed on Myeloid Cells 1) signaling was also activated in heat-stressed liver tissues and is implicated in liver inflammation and fibrosis by promoting hepatic inflammation, activating stellate cells, and serving as a master regulator of Kupffer cell activation and linked to inflammation, lipid accumulation, fibrosis, and tumor progression in liver-related diseases 63 .…”
Section: Discussionmentioning
confidence: 99%
“…Pathway enrichment study identified the activation of NOD1/NOD2 in liver tissues of the heat stress group which triggers proinflammatory and type I interferon responses, contributing to liver injury. These receptors play a role in recognizing bacterial pathogens, inducing liver inflammation, and have associations with innate immune activation in metabolic diseases, with studies suggesting that blocking NOD1 can be protective against tissue injury 61 , 62 . TREM-1 (Triggering Receptor Expressed on Myeloid Cells 1) signaling was also activated in heat-stressed liver tissues and is implicated in liver inflammation and fibrosis by promoting hepatic inflammation, activating stellate cells, and serving as a master regulator of Kupffer cell activation and linked to inflammation, lipid accumulation, fibrosis, and tumor progression in liver-related diseases 63 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, RNA-seq analysis suggested that Ala might also regulate the NOD-like signaling pathway. Studies have shown that a high-fat diet causes intestinal leakage and activates NOD1 and NOD2 in organs [ 39 ]. Also, the expression of both NOD1 and NOD2 was upregulated in HFD mice [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The recognition of Microbe-Associated Molecular Pattern (MAMP) by NOD1 has been demonstrated to impact hepatocarcinogenesis and the development of liver damage ( 47 ). Furthermore, NOD1 has been found to upregulate the tumorigenicity of human cervical squamous cell carcinoma, thereby promoting cancer progression and metastasis ( 48 ).…”
Section: Discussionmentioning
confidence: 99%